STRATEGI DIGITALISASI EKONOMI PURWOKERTO DALAM PENERAPAN SMART CITY - Khanin Nurrohmah; Mohammad Radita Restu Mahendra; Alfina Nur Hidayati; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research examines the digital economy digitalization strategy of Purwokerto in the implementation of a smart city that is not yet uniform; many areas in Purwokerto lag behind in digitalization systems. This study uses a qualitative approach with data analysis techniques through literature studies. The qualitative approach was chosen because it aligns with the research objectives, particularly in understanding the meanings contained in the data or social interactions of a phenomenon and identifying patterns of relationships that emerge in analyzing the basic concepts of smart city used in Purwokerto. The digital economic strategy in Purwokerto in the implementation of a smart city. To encourage the realization of the smart city concept in the Purwokerto area, various strategies have begun to be implemented, including strengthening digital infrastructure, developing technology-based public services, and enhancing the digital capabilities of MSME actors through training and the use of online platforms. Local governments are also beginning to integrate technology into environmental management and build cross-sector collaborations, including with universities and technology communities. Although the process is still in the development stage, these steps signify Purwokerto's commitment to becoming a smarter, more efficient, and adaptive city to the needs of its citizens.